IChoose Kidney for Treatment Options: Updated Models for Shared Decision Aid. Issue 9 (September 2018) - Gander, Jennifer C.; Basu, Mohua; McPherson, Laura; Garber, Michael D.; Pastan, Stephen O.; Manatunga, Amita; Arriola, Kimberly Jacob; Patzer, Rachel E.
Abstract : Supplemental digital content is available in the text.